Pengaruh Pengetahuan Perpajakan, Pemahaman Wajib Pajak, Sanksi Perpajakan, Persepsi Wajib Pajak Dan Motivasi Wajib Pajak Terhadap Minat Menggunakan Jasa Konsultan Pajak (Studi Kasus Pada Kantor Wilayah DJP SUMUT 1) - Sonia Ananda; Rizki Fillhayati Rambe; Syamsul Bahri Arifin (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
This research aims to determine taxation knowledge, taxpayer understanding, tax sanctions, taxpayer perceptions, and taxpayer motivation on interest in using tax consultant services at the DGT SUMUT I Regional Office. The sample selection technique used is convenience sampling. The total observations in this research were 100 taxpayers. The data analysis technique used in this research is multiple linear analysis. The test results of this research indicate that together tax knowledge, taxpayer understanding, tax sanctions, taxpayer perceptions, and taxpayer motivation affect the interest in using tax consultant services. Partially, tax knowledge, understanding of taxpayers, tax sanctions, taxpayer perceptions affect the interest in using tax consultant services. Meanwhile, taxpayer motivation has no effect on interest in using tax consultant services.